Reinforcing Mothers’ Nutritional Knowledge to Combat the Spread of Non-Communicable Diseases: Food-Based Dietary Guidelines - Yolisa Christina Majija (E-Journal of Humanities, Arts and Social Sciences)
The primary objective of this study was to examine the firsthand experiences and perspectives of expectant mothers regarding the incorporation of food-based dietary guidelines into their daily routines as a means of reducing the risk of specific non-communicable diseases (NCDs) such as diabetes, obesity, and cardiovascular diseases for both themselves and their children. The 2020 UNICEF Conceptual Framework on the Determinants of Maternal and Child Nutrition served as the foundation for this investigation. Utilizing a case study design within an interpretive research paradigm, this study sought to assess how reinforcing maternal nutritional knowledge, guided by Food-Based Dietary Guidelines (FBDGs), could help reduce the prevalence of these NCDs during early childhood. A group of 10 individuals was selected using purposive sampling, and a qualitative approach was employed to gather insights. The study revealed that many survey participants were unaware of the South African Food-Based Dietary Guidelines (SA FBDGs). Some mentioned their search for official guidelines from SA FBDGs, while others referred to the four dietary categories. Limited overall health knowledge” and “lack of awareness among parents were discovered. Considering these findings, the research suggested that nutritional education should start in primary school. In collaboration with health and nutrition experts, it proposed that the Department of Education consider introducing such programs in Early Childhood Development Centres before elementary school. It is essential to emphasize the government’s importance in ensuring appropriate educational interventions are implemented. Increasing knowledge about nutrition through education and interventions may help reduce the risk of chronic diseases and enhance overall health.